Champions of digital transformation? The dynamic capabilities of hidden champions - Daniel Wittenstein (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
Hidden Champions (HCs) are small- and medium-sized global market leaders that repeatedly show superior innovation capabilities and economic performance. However, empirical evidence on how the digital transformation may affect their success story remains scarce. I argue that HCs show stronger dynamic capabilities which enables them to be better prepared for the digital transformation than non-HCs firms. To test this hypothesis, I use data from the Mannheim Innovation Panel. This allows me to identify a representative set of German HCs and develop a firm digital readiness index, reflecting the use of important digital technologies and applications. An instrumental variable estimation suggests that higher levels of digital readiness lead to an increase in share of revenue from innovations and productivity. In combination with higher average digital readiness levels of HCs compared to non-HCs, my findings indicate that HCs may indeed be better prepared for the digital transformation.
Keywords: L60; L19; M19; O32; O33; 330; hidden champions; digital transformation; digital readiness; digital preparedness; performance effects; innovation; dynamic capabilities; instrumental variable estimation